Advanced materials modeling for structure - Altenbach, Holm, 1956-; Kruch, Serge (Berlin: Springer, 2013)
This volume presents the major outcome of the IUTAM symposium on'Advanced Materials Modeling for Structures'. It discusses advances in high temperature materials research, and also to provides a discussion the new horizon of this fundamental field of applied mechanics. The topics cover a large domain of research but place a particular emphasis on multiscale approaches at several length scales applied to non linear and heterogeneous materials. Discussions of new approaches are emphasised from various related disciplines, including metal physics, micromechanics, mathematical and computational mechanics.
Viscoplastic constitutive model to divide inelastic strain into time-independent and time-dependent strains / Ken-ichi Ohguchi, Katsuhiko Sasaki -- Multiaxial low cylce fatigue for Ni-base single crystal super alloy at high temperature / Masao Sakane...[et al.] -- Mechanics of materials for microelectronic components and packages / Vadim V. Silberschmidt -- Constitutive models for the description of creep and plasticity of cast and wrought Mg-Al and Mg-Zn alloys / Stefano Spigarelli, Mohammad El Mehtedi, A. Di Salvia -- Deformation and failure of various alloys under creep-fatigue loading and their modelling / Yukio Takahashi -- The effect of temperature on interfacial gradient plasticity in metallic thin films / George Z. Voyiadjis, Danial Faghihi -- A cyclic crystal viscoplastic model considering both dislocation slip and twinning / Cao Yu...al.].
Titre de l'ran-titre (visionnle 12 mars 2013).
Bibliographies.
Keywords: Construction -- Materiaux -- Congres; Materiaux -- Proprietes mecaniques -- Congres